Prevention of gender-based violence in climate crises: entrenching feminist finance - Bhardwaj, Vani (Frontiers in Global Women's Health, 2025)
The climate finance architecture addresses mitigation, adaptation, and loss and damage for climate-resilient development. However, it fails to advance the debt-related injustices in climate financing that inflict economic and non-economic violence on women from the low- and middle-income countries (LMICs) and marginalized communities in the “Global North.” Gender-based violence (GBV) is one dimension of climate injustices that becomes a risk multiplier to the lives of women, girls, and gender minorities across race, caste, abilities, and ethnicities. This article establishes the climate-resilient gender-responsive solutions to internalize gender-based violence prevention in the feminist economy of climate finance. Resultantly, the care economy under climate crises transforms family structures and relations beyond the neoclassical comprehension of micro and macroeconomics. This article takes a multisectoral approach to gender-responsive finance for climate crises. Moreover, it draws on gray literature from civil society organizations and think tanks addressing the majority of perspectives and academic articles across principles of feminist economics, climate financing, and gender-based violence.